Parkinson’s Critical Heart Rate Test: Applying the Critical Power Model for People with Parkinson’s Disease - Barbieri, Ricardo Augusto; Kalva-Filho, Carlos Augusto [UNESP]; Faria, Murilo Henrique [UNESP]; Silveira-Ciola, Aline Prieto [UNESP]; Torriani-Pasin, Camila; Simieli, Lucas [UNESP]; Barbieri, Fabio Augusto [UNESP] (Termedia Sp. z.o.o., 2024)
Aerobic exercise with the correct intensity can attenuate motor and non-motor symptoms of Parkinson's disease (PD) and improve the quality of life. However, a specific, validated, non-invasive, and outside the laboratory protocol that assesses physiological variables to prescribe optimal aerobic exercise intensity for people with PD is nonexistent. Therefore, this study aimed to propose a protocol, the Parkinson's critical heart rate test (Parkinson-CHR test), to determine the critical heart rate (CHR) in individuals with PD and verify its validity, reliability, and sensitivity. Fifteen people with idiopathic PD, who were able to practice exercises, were recruited to participate in the study (71.1 ± 6.6 years). The study consisted of two experiments: i) the first one aimed to assess the validity and reliability of the protocol, with participants performing the test twice at a one-week interval; ii) the second experiment aimed to investigate the protocol sensitivity, with individuals being evaluated before and after an 8-week training program according to Parkinson-CHR intensity. In experiment 1, no differences between test and retest were observed in the time to cover the distances (400, 800 and 1200 m), the total heart rate, the critical heart rate, and critical speed (p > 0.05). In experiment 2, there was a reduction in time to cover 400 and 800 m as well as in the total heart rate for all distances after the 8-week training program. The Parkinson-CHR test is a reliable, reproducible, inexpensive, and non-invasive protocol to assess, prescribe, and monitor aerobic exercise intensity in people with PD.
Keywords: aerobic exercise; exercise intensity; reliability; testing; validity